Literature Review on Economic Effects of the RCEP - Liu, Shuning (Transactions on Economics, Business and Management Research, 2024)
Since the outbreak of the COVID-19 pandemic, there have been significant fluctuations in the global economy and trade, leading to a pivotal moment in the global economic system. In this context, the Regional Comprehensive Economic Partnership (RCEP) has been officially established, showing positive effects on trade activities and economic progress among its member nations. This study systematically reviews the relevant literature on RCEP and draws the following conclusions: First, RCEP was formed against the backdrop of global economic and trade turbulence and holds significant implications for fostering economic and trade growth in the East Asian region, as well as advancing the process of Asian integration. Second, upon reviewing the literature on RCEP, it was observed that the majority of current literature concentrates on the national level, with less emphasis on the firm level. At the national level, the literature primarily focuses on trade exchange and international investment. Last, most of the literature concerning the impact areas of the RCEP concentrates on international trade and direct investment, while there is still significant potential for research on the mechanisms and potential negative consequences of indirect investment and international trade, as well as sustainable development in emerging research areas.